2007
DOI: 10.1002/hed.20711
|View full text |Cite
|
Sign up to set email alerts
|

Endodermal sinus tumor of the paranasal sinuses

Abstract: Because of the rarity of this entity, no standardized treatment protocol has been defined. The involvement of the anterior skull base in our case necessitated a radical craniofacial resection, despite a partial response to chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
1
11
0
Order By: Relevance
“…In the sinonasal tract, nasopharynx, and oral cavity, some 30 cases of teratocarcinosarcoma with unusual neuroectodermal elements have been reported (6,7,19,20). Their similarities with the present case reside in their presentation in a similar advanced age group, malignant behavior, and histology containing areas of unusual elements such as squamous carcinoma, rhabdomyosarcoma, and malignant neurologic components.…”
supporting
confidence: 49%
See 1 more Smart Citation
“…In the sinonasal tract, nasopharynx, and oral cavity, some 30 cases of teratocarcinosarcoma with unusual neuroectodermal elements have been reported (6,7,19,20). Their similarities with the present case reside in their presentation in a similar advanced age group, malignant behavior, and histology containing areas of unusual elements such as squamous carcinoma, rhabdomyosarcoma, and malignant neurologic components.…”
supporting
confidence: 49%
“…It would seem that perhaps some of the reported sinonasal teratocarcinosarcoma cases could have a germ cell origin, a hypothesis supported by their age of presentation and midline situation, which is a characteristic location for germ cell tumors. Indeed, some of the YSTs reported in children are likely to be of germ cell origin (20).…”
mentioning
confidence: 99%
“…1 The prognosis of patients, especially children with ESTs, is unknown, although there have been reports of successful management by surgery, radiotherapy, and adjuvant chemotherapy (cisplatin, bleomycin, and vinblastine). 10,[16][17][18] Weedon and Musgrave 19 described a female infant who had an YST in the maxillofacial area that was diagnosed at the age of 10 months, and she died 1 month later. Margo et al 14 reported 5 cases of YSTs of the orbit occurring in children 3 months to 4 years old.…”
Section: Discussionmentioning
confidence: 98%
“…To our knowledge, adult YST in the nasal area is very rare, and only six cases have been reported in the English literature. YSTs of the nasal cavity and paranasal sinuses in children are mostly pure YSTs, while those in adults are mostly accompanied by cancer, such as teratocarcinosarcoma or choriocarcinoma, [4][5][6][7]12,13 suggesting that YSTs of the nasal cavity and paranasal sinuses in adults may originate from somatic cells.…”
Section: Discussionmentioning
confidence: 99%
“…4 Unlike YSTs in children with pure YST morphology, YSTs in adults are frequently accompanied by cancer, teratocarcinosarcoma, and other components. [4][5][6][7] Here, we have reported a case of a neoplasm with a morphology and immunophenotype of pure YST. However, SMARCB1 (INI-1) immunohistochemical staining and fluorescence in situ hybridization (FISH) revealed SMARCB1 (INI-1)-deficient carcinoma.…”
Section: Introductionmentioning
confidence: 98%